Faktor – Faktor Yang Mempengaruhi Kinerja Manajerial pada KSP Melati Jaya, Bondowoso - Riki Junior; Diana Dwi Astuti; Hamzah Fansuri Yusuf (JAKUMA : JURNAL AKUNTANSI DAN MANAJEMEN KEUANGAN, 2023)
This study aims to determine the effect of accountability, budgetary participation, clarity of budget targets, locus of control, and internal control systems on managerial performance at the Jasmine Jaya Bondowoso cooperative. The method used in this research is by distributing questionnaires. The population in this study were employees of the Jasmine Jaya Bondowoso cooperative. The sample used in this study used a saturated sample so that a sample of 25 people was obtained. The data analysis method used is multiple linear regression. The results showed that accountability, budget participation, clarity of budget targets, and internal control systems partially affected the managerial performance of the Jasmine Jaya Bondowoso cooperative. While the locus of control does not partially affect the managerial performance of the Jasmine Jaya Bondowoso cooperative. Simultaneously accountability, budget participation, clarity of budget targets, locus of control, and internal control systems affect the managerial performance of the Jasmine Jaya Bondowoso cooperative.